PENGALAMAN PASIEN HIPERTENSI LANSIA SELAMA COVID-19 DI DESA SEI BULUH KECAMATAN TELUK MENGKUDU KABUPATEN SERDANG BEGADAI - Dewi Adinda Sari; Rostime Hermayerni Simanullang (Indonesian Trust Nursing Journal, 2026)
Hypertension is known as "the silent killer," where sufferers are unaware that they have hypertension. This condition occurs because symptoms are not felt until the sufferer is aware that their blood pressure is too high and complications that can lead to death may have occurred and numbers continue to rise each year, have become a concern during the COVID-19 pandemic. This objective is to explore the meaning of the experiences of elderly hypertension patients during the Covid-19 pandemic. This research uses a qualitative type with a phenomenological design. In this study, the researcher used 7 participants. The data analysis techniques used by the researcher are (1) data reduction, (2) data display, and (3) drawing conclusions. The results of this study are in the form of 4 themes related to the experiences of elderly hypertension patients during the Covid-19 pandemic, including: (1) elderly knowledge about hypertension, (2) ability to handle hypertension, (3) strategies for controlling hypertension, (4) obstacles to handling hypertension. The conclusions in this study are: (1) Elderly people who have a history of hypertension are able to understand hypertension, (2) Elderly people are able to treat hypertension early when they start to experience hypertension, (3) Elderly people know what actions they should take to control hypertension, (4) Elderly people know what obstacles or constraints they often experience when they experience hypertension.